The Influence of Football Coach Competition on Athlete Achievement Results - Hendra, Toni; Nuraini, Tryna; Widowati, Atri; Munar, Hendri (International Journal of Educational Dynamics, 2024)
Football is a very popular sport and in demand by people worldwide, including Indonesia. However, the current achievements of Indonesian football are not yet impressive. One factor thought to influence soccer athletes' performance is competition and the quality of coaches. This research aims to determine the effect of soccer coach competition on athlete achievement results. The research method used is a literature study by analyzing related literature. The research results show that soccer coach competitions have a significant influence on athlete performance results. The higher the level of competition the coaches participate in, the better the athlete's performance results will be. This is because coaches who have experience participating in high competition will have better knowledge, skills, and coaching abilities. The implication of this research is the need for efforts to increase the competence of football coaches through increasing the level of competition they participate in, as well as adequate support and coaching from related parties that Indonesian football achievements can improve.